Effect of Comorbid Metabolic Syndrome and Related Components on Cognition in Patients with Schizophrenia - (:unkn) unknown (YERKURE TANITIM & YAYINCILIK HIZMETLERI A S, 2018)
Objective: The aim of the present study is to compare the cognitive functions of patients with and without metabolic syndrome (MetS) in schizophrenia and schizoaffective disorder, and to investigate the relationship between the clinical symptomatology and MetS-related components with cognitive functions. Methods: This cross-sectional study included 79 patients diagnosed with schizophrenia/schizoaffective disorder. All participants were assessed using the Positive PANSS and a neurocognitive battery to assess memory, attention and executive function. Results: In the study group, 35 (44.30%) patients met the criteria for MetS. The MetS group performed worse than those without MetS on verbal memory subtests. There was no difference in attention and executive functioning of the Mets and non-MetS groups. Multiple regression analyses showed that, elevated HDL were significantly associated with better scores for verbal memory, visual memory, and executive functions. In contrast, a higher BMI was significantly associated with poorer scores on visual memory, verbal memory, attention and executive functioning. Unexpectedly, a greater waist circumference was associated with better scores for executive functioning. Discussion: MetS and related components are associated with impaired cognitive functioning in patients with schizophrenia/ schizoaffective disorder. Early interventions such as reducing risk related BMI values or increasing HDL levels, may reduce risk factors for MetS and have positive effects on cognitive functioning in patients with schizophrenia.
Keywords: Attention; cognitive function; executive function; metabolic syndrome; memory; schizophrenia; verbal memory